CytoSorb in patients with coronavirus disease 2019: A rapid evidence review and meta-analysis - Wei, Shilin; Zhang, Yanchun; Zhai, Kerong; Li, Jian; Li, Mingming; Yang, Jianbao; Zhang, Rongzhi; Li, Yongnan; Li, Zhenzhen (Frontiers in Immunology, 2023)
Background: After its approval by the European Union in 2011, CytoSorb therapy has been applied to control cytokine storm and lower the increased levels of cytokines and other inflammatory mediators in blood. However, the efficiency of this CytoSorb treatment in patients with coronavirus disease (COVID-19) still remains unclear. To elucidate the Cytosorb efficiency, we conducted a systematic review and single-arm proportion meta-analysis to combine all evidence available in the published literature to date, so that this comprehensive knowledge can guide clinical decision-making and future research. Methods: The literature published within the period 1 December 2019 to 31 December 2021 and stored in the Cochrane Library, Embase, PubMed, and International Clinical Trials Registry Platform (ICTRP) was searched for all relevant studies including the cases where COVID-19 patients were treated with CytoSorb. We performed random-effects meta-analyses by R software (3.6.1) and used the Joanna Briggs Institute checklist to assess the risk of bias. Both categorical and continuous variables were presented with 95% confidence intervals (CIs) as pooled proportions for categorical variables and pooled means for continuous outcomes. Results: We included 14 studies with 241 COVID-19 patients treated with CytoSorb hemadsorption. Our findings reveal that for COVID-19 patients receiving CytoSorb treatment, the combined in-hospital mortality was 42.1% (95% CI 29.5–54.6%, I2 = 74%). The pooled incidence of adjunctive extracorporeal membrane oxygenation (ECMO) support was 73.2%. Both the C-reactive protein (CRP) and interleukin-6 (IL-6) levels decreased after CytoSorb treatment. The pooled mean of the CRP level decreased from 147.55 (95% CI 91.14–203.96) to 92.36 mg/L (95% CI 46.74–137.98), while that of IL-6 decreased from 339.49 (95% CI 164.35–514.63) to 168.83 pg/mL (95% CI 82.22–255.45). Conclusions: The majority of the COVID-19 patients treated with CytoSorb received ECMO support. In-hospital mortality was 42.1% for the COVID-19 patients who had CytoSorb treatment. Both CRP and IL-6 levels decreased after Cytosorb treatment.